2020
DOI: 10.31488/bjcr.141
|View full text |Cite
|
Sign up to set email alerts
|

Immune Attack against Breast Cancer Revealed in Patient Tumor Sections by Memristive Nanowire Sensors

Abstract: A foundational principle of tumor immunology is that cancer cells can be eliminated by host cytotoxic T lymphocytes. This T lymphocyte immune attack can be potentiated by novel treatment modalities called immunotherapies and, patient tumors with pre-existing immune attack are more responsive to immunotherapies. However, cancers often hijack immune attack and precision oncology seeks for decision-making tools that are able to identify immune attack in minute amounts of patient tumor biopsies. Silicon nanowire m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The demonstrated sensitivity in many cases has achieved the femtomolar (Puppo et al, 2013(Puppo et al, , 2014Shalev et al, 2013;Ibarlucea et al, 2018) or even attomolar levels (Patolsky et al, 2006b;Buitrago et al, 2014;Tzouvadaki et al, 2016), with an ultimate resolution of single-analyte binding events (Patolsky et al, 2004). The published works have shown that detection in hostile environments such as breast cancer tissue (Tuoheti et al, 2020), blood plasma (Nguyen-Le et al, 2022, or saliva (Klinghammer et al, 2020) is possible. The latter aimed at cortisol hormones as target, showing that such platforms hold great promise for monitoring DA in other body fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The demonstrated sensitivity in many cases has achieved the femtomolar (Puppo et al, 2013(Puppo et al, , 2014Shalev et al, 2013;Ibarlucea et al, 2018) or even attomolar levels (Patolsky et al, 2006b;Buitrago et al, 2014;Tzouvadaki et al, 2016), with an ultimate resolution of single-analyte binding events (Patolsky et al, 2004). The published works have shown that detection in hostile environments such as breast cancer tissue (Tuoheti et al, 2020), blood plasma (Nguyen-Le et al, 2022, or saliva (Klinghammer et al, 2020) is possible. The latter aimed at cortisol hormones as target, showing that such platforms hold great promise for monitoring DA in other body fluids.…”
Section: Introductionmentioning
confidence: 99%